The effect of leaving employment on mental health: Testing 'adaptation versus sensitisation' in a cohort of working-age Australians - Milner, A; Spittal, M; Page, A; Spittal, MJ; LaMontagne, AD (My University, 2013)
Objectives To investigate the ‘adaptation’ versus ‘sensitisation’ hypotheses in relation to mental health and labour market transitions out of employment to determine whether mental health stabilised (adaptation) or worsened (sensitisation) as people experienced one or more periods without work. Methods The Household Income and Labour Dynamics of Australia (HILDA) longitudinal survey was used to investigate the relationship between the number of times a person had been unemployed or had periods out of the labour force (ie, spells without work) and the Mental Component Summary (MCS) of the Short Form 36 (SF-36). Demographic, health and employment related confounders were included in a series of multilevel regression models. Results During 2001–2010, 3362 people shifted into unemployment and 1105 shifted from employment to not in the labour force. Compared with participants who did not shift, there was a 1.64-point decline (95% CI −2.05 to −1.23, p<0.001) in scores of the MCS SF-36 among those who had one spell of unemployment (excluding not in the labour force), and a 2.56-point decline (95% CI −3.93 to −1.19, p<0.001) among those who had two or more spells of unemployment after adjusting for other variables. Findings for shifts from employment to ‘not in the labour force’ were in the same direction; however, effect sizes were smaller. Conclusions These results indicate that multiple spells of unemployment are associated with continued, though small, declines in mental health. Those who leave employment for reasons other than unemployment experience a smaller reduction in mental health.
Keywords: Employment -- Labour force status and attachment; Health -- Mental; Labour market; Health and wellbeing; Employment; Health; Labour force status and attachment; Mental; Employment and unemployment; Health and wellbeing